EMI/EMC issues in power system and power electronic circuits : part I - Sie, Dominic Yong Chin. (2010)
The operating frequency of switched-mode power electronic circuits can be as high as 1MHz. With such a high operating frequency, the electromagnetic interference posed by it to its ambient devices may need to be concerned. Furthermore the radiation by the high frequency pulse can make the device fail in the test according to EMC/EMI standards, such as IEC standards. In this project, the researcher will calculate the radiation by a designed power electronic circuit operating at high-frequency and measure its radiative pollution to its ambient. The technique to suppress the radiation will be explored as well.